Draft Genome Sequence of Bacillus thuringiensis Strain m401, Isolated from Honey in Argentina - Abrahamovich, Eliana (2018)
We report here the 6,092,003-bp draft genome sequence of Bacillus thuringiensis strain m401, a tetracycline-resistant isolate recovered from honey. The isolate contained three plasmids of 8,307 bp, 9,934 bp, and 69,561 bp and a tetracycline resistance gene with high homology to tet45 in a contig of 236,180 bp.